(untitled) (Swiss Medical Weekly, 2021)
INTRODUCTION Although recommended, the implementation of early advance care planning is suboptimal in amyotrophic lateral sclerosis (ALS) patients. Barriers to advance care planning include healthcare professionals’ and patients’ reluctance, and uncertainty about the right time to initiate a discussion. AIM OF THE STUDY To determine how often advance care planning was initiated, and the content of the discussion in a first routine palliative care consultation integrated within a multidisciplinary management programme. METHODS Between June 2012 and September 2016, a prospective cohort study was conducted in Geneva University Hospitals. Sixty-eight patients were seen every 3 months for a 1-day clinical evaluation in a day care centre. RESULTS The patients’ mean ± standard deviation age was 68.6 ± 11.9 years, 50% were women. Four patients were excluded because of dementia. Advance care planning was initiated with 49 (77%) patients in the first palliative care consultation. Interventions most often addressed were cardiopulmonary resuscitation (49%), intubation and tracheostomy (47%) and palliative sedation (36.7%). Assisted suicide was discussed with 16 patients (36.6%). Functional disability was the only factor associated with initiation of advance care planning. Nearly half of the patients wrote advance directives (45%) or designated a healthcare surrogate (41%). Bulbar onset, functional disability and noninvasive ventilation were not associated with the completion of advance directives. CONCLUSION Early initiation of advance care planning is feasible in most ALS patients during a routine consultation, and relevant treatment issues can be discussed. All ALS patients should be offered the opportunity to write advance directives as completion was not associated with disease severity. (Registered at clinicaltrials.gov: No. NCT03536962.)